PENGARUH INDEPENDENSI, MOTIVASI, KOMITMEN ORGANISASI, PENGALAMAN, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA AUDITOR BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN PERWAKILAN PROVINSI RIAU - Ferby Mutia Edwy; Amir Hasan; Kamaliah Kamaliah (Program Studi Pendidikan Ekonomi Universitas Riau, 2019)
This study aimed to determine: (1) the influence of independence on auditor’sperformance at BPKP of Riau Province, (2) the influence of motivation on auditor’sperformance at BPKP of Riau Province, (3) the influence of organizationalcommitment on auditor’s performance at BPKP of Riau Province, (4) the influence ofexperience on auditor’s performance at BPKP of Riau Province, (5) the influence ofleadership style on auditor’s performance at BPKP of Riau Province. Therespondents are auditors who work at BPKP of Riau Province. The samples usedcensus method, and the whole was used as the samples. Data was collected byquestionnaire delivered directly. 99 questionnaire was distributed, but only 82questionnaire were returned. The hypothesis was tested by using multiple linearregression analysis with a SPSS (Statistical Package for Social Science) softwareprogram. The result showed that: 1) independence has significant influence onauditor’s performance, 2) motivation has significant influence on auditor’sperformance, 3) organizational commitment has significant influence on auditor’sperformance, 4) experience has significant influence on auditor’s performance, 5)leadership style has significant influence on auditor’s performance. The coefficient ofdetermination shows that the effect of independence, motivation, organizationalcommitment, experience and leadership style on auditor’s performance amounted to60%.